Answer:
-23
Step-by-step explanation:
We are given the functions;
h(x) = 5x - 3 and j(x) = -2x
Now, we want to find h[j(2)]
j(2) = -2(2)
j(2) = -4
Thus;
h(-4) = 5(-4) - 3
h(-4) = -20 - 3
h(-4) = - 23
Answer:
D
Step-by-step explanation:
11.1/0.01=11.1*100=1110
Answer:
x = 8
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define equation</u>
3(x - 2) = 2(x + 1)
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute: 3x - 6 = 2x + 2
- Subtract 2x on both sides: x - 6 = 2
- Add 6 to both sides: x = 8
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: 3(8 - 2) = 2(8 + 1)
- Subtract/Add: 3(6) = 2(9)
- Multiply: 18 = 18
Here we see that 18 does indeed equal 18.
∴ x = 8 is a solution to the equation.
As for a specific equation, I could not say. However, I can tell you how to find x!
The first thing to remember is that a straight line has a 180 degree angle.
You see on the bottom side that we have a 146 degree angle. Now look at the top side. Look closely, and you will see that the two sides are actually identical!
Don't see it? Look at the line on top between x and 56, and imagine it is not there. You see that we actually have the same 146 degree angle, just flipped right side up!
However, this angle does not say 146, but makes an extra line between them with x and 56. This means that x + 56 equals 146!
So we can find x by subtracting 56, from 146, which is... 90!
Add all the item together:
16 + 28 + 12 + 4
=60 total items